Organocatalytic Asymmetric Tandem α‐Aminooxylation–Henry Reactions for the Synthesis of 1, 2‐Diols: Total Synthesis of (–)‐l‐threo‐Sphinganine. Issue 45 (30th November 2017) - Garg, Yuvraj; Kaur, Ramandeep; Kumar Pandey, Satyendra
Abstract : A new and rapid asymmetric synthesis of anti ‐ and syn ‐β, γ‐dihydroxynitroalkanes through an organocatalytic tandem α‐aminooxylation–Henry reaction is described. The target diol derivatives were synthesized in good yields, with excellent enantioselectivities, and low to moderate diasteroselectivities, under mild conditions. The synthesis of the antineoplastic and antipsoriatic drug (–)‐l ‐ threo ‐sphinganine demonstrates the synthetic utility of the building blocks generated in the developed reaction. Abstract : The asymmetric synthesis of anti ‐ and syn ‐β, γ‐dihydroxynitroalkanes from aldehydes through an organocatalytic tandem α‐aminooxylation–Henry reaction is reported. The reaction was also applied to the total synthesis of the antineoplastic and antipsoriatic drug (–)‐l ‐ threo ‐sphinganine.